Inhibition of UII/UTR system relieves acute inflammation of liver through preventing activation of NF-κB pathway in ALF mice. - Dong-yu Liang (Public Library of Science (PLoS), 2014)
Urotensin II (UII) is implicated in immune inflammatory diseases through its specific high-affinity UT receptor (UTR). Enhanced expression of UII/UTR was recently demonstrated in the liver with acute liver failure (ALF). Here, we analysed the relationship between UII/UTR expression and ALF in lipopolysaccharide (LPS)/D-galactosamine (GalN)-challenged mice. Thereafter, we investigated the effects produced by the inhibition of UII/UTR system using urantide, a special antagonist of UTR, and the potential molecular mechanisms involved in ALF. Urantide was administered to mice treated with LPS/GalN. Expression of UII/UTR, releases of proinflammatory cytokines including tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and interferon-γ (IFN-γ), and activation of nuclear factor κB (NF-κB) signaling pathway were assessed in the lethal ALF with or without urantide pretreatment. We found that LPS/GalN-challenged mice showed high mortality and marked hepatic inflammatory infiltration and cell apoptosis as well as a significant increase of UII/UTR expression. Urantide pretreatment protected against the injury in liver following downregulation of UII/UTR expression. A close relationship between the acutely flamed hepatic injury and UII/UTR expression was observed. In addition, urantide prevented the increases of proinflammatory cytokines such as TNF-α, IL-1β and IFN-γ, and activation of NF-κB signaling pathway induced by LPS/GalN in mice. Thus, we conclude that UII/UTR system plays a role in LPS/GalN-induced ALF. Urantide has a protective effect on the acutely inflamed injury of liver in part through preventing releases of proinflammatory cytokines and activation of NF-κB pathway.